The Impact of Entrepreneurial Alertness on Enhancing Competitive Advantage: A Field Study of a Sample of Tourism Company Managers in Baghdad City (Al-Mansour Journal, 2026)
This study investigates the strategic nexus between Entrepreneurial Alertness (EA) and Competitive Advantage (CA) within the tourism sector in Baghdad. It establishes a comprehensive theoretical and operational framework designed to assist firms in identifying market contingencies and converting them into sustainable competitive edges amid an increasingly volatile business landscape. The research problem highlights a significant lag in the responsiveness of local tourism entities to global market transformations, primarily due to the persistence of conventional management paradigms that lack the requisite "vigilance" to capitalize on emerging opportunities. This inertia has compromised their market position against international conglomerates and digital disruptors. Adopting a descriptive-analytical approach, the study surveyed a purposive sample of (108) executive managers and decision-makers. Data were processed using SPSS (v.25) and Amos (v.25), employing Structural Equation Modeling (SEM) for hypothesis testing. The findings underscore that fostering "Entrepreneurial Intuition" is no longer optional but a strategic imperative for leadership. Specifically, the results indicate that organizations exhibiting proactive alertness toward disruptive technologies—notably Artificial Intelligence (AI) and Augmented Reality (AR)—consistently outperformed their rivals. Conversely, a critical deficit was identified in the strategic mobilization of latent resources to exploit newfound opportunities The research advocates for the institutionalization of "Entrepreneurial Vigilance" through the integration of advanced market intelligence systems and the cultivation of strategic alliances with academic and professional bodies. Furthermore, the study emphasizes the necessity of a radical digital pivot and the alignment of human capital development with global benchmarks to ensure enduring competitive excellence.
Keywords: entrepreneurial preparedness; competitive ability; tourism companies; dimensions of competitive ability; competitive advantage